A Study on Second Harmonic Excitation in Electron Beam–Plasma Instability - Rafiei, Maryamsadat; Sahrai, Mostafa; Hosseinpour, Mahboub; Esfandyari-Kalejahi, Abdolrasoul (Frontiers in Astronomy and Space Sciences, 2022)
The effect of ion dynamics on the generation of electromagnetic waves in the second harmonic of electron plasma frequency during warm electron beam-plasma instability is investigated using 2D electromagnetic particle-in-cell simulations. We consider four cases: A: mi/me = 0 (two electron stream instability); B: mi/me = 1 (background pair plasma); C: mi/me = 100 and D: mi/me = 1000. It is shown that the generation of Langmuir waves in the fundamental mode of electron plasma frequency and the subsequent dynamics of large amplitude solitons are not affect by the ion species. However, it determines the decay process of solitons and the excitation of electromagnetic waves in the second harmonic. In the first two cases, mi/me =0 and 1, there is no sign of emission in the second harmonic, whereas the strongest emission of second harmonic is found for the case of largest mass ratio, mi/me =1000. This confirms the two-step wave-wave coupling mechanism for the generation of second harmonic electromagnetic waves, which requires the excitation of ion acoustic waves in the first step. Moreover, the dispersion diagrams of all excited waves are presented.